Radiographic patterns and associations of osteoarthritis of the knee in patients referred to hospital. Issue 7 (July 1993) - Ledingham, J; Regan, M; Jones, A; Doherty, M
Abstract : OBJECTIVES–To investigate differing patterns and associations of osteoarthritis of the knee in patients referred to hospital. METHODS–Two hundred and fifty two consecutive patients (161 women, 91 men; mean age 70 years, range 34-91 years) referred to hospital with osteoarthritis of the knee underwent clinical, radiographic, and synovial fluid screening. RESULTS–Radiographic changes of osteoarthritis of the knee (definite narrowing with or without osteoarthritic features) were bilateral in 85% of patients. Of 470 knees affected, 277 (59%) were affected in two compartments and 28 (6%) in three compartments. Unilateral and isolated medial tibiofemoral osteoarthritis were more common in men. Calcium pyrophosphate crystal deposition was common (synovial fluid identification in 132 (28%) knees; knee chondrocalcinosis in 76 (30%) patients) and associated with disability, bilateral, multicompartmental and severe radiographic osteoarthritis, marked osteophytosis, attrition, and cysts. Multiple clinical nodes (58 (23%) patients) and radiographic polyarticular interphalangeal osteoarthritis (66 (26%) patients) were associated with a higher frequency of inactivity pain, disability, multicompartmental and severe radiographic change. Forestier's disease predominated in men but showed no other associations. CONCLUSIONS–In a group of patients referred to hospital osteoarthritis of the knee is usually bilateral and affects more than one compartment. Severe and multicompartmental radiographic changes are associated with calcium pyrophosphate crystal deposition, nodal change, and polyarticular interphalangeal osteoarthritis.